Nutritional status trajectories in cured and non-cured pediatric tuberculosis patients following six-month anti-TB treatment - Zulfahlayya Zulkifli; Bakhtiar Bakhtiar; Eka Yunita Amna; Heru Noviat Herdata; Mulya Safri; Darnifayanti Darnifayanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Pediatric tuberculosis (TB) remains a critical public health issue in Indonesia, with 809,000 new cases reported in 2023. Malnutrition is a common comorbidity; however, the nutritional trajectory that differentiates children who achieve clinical recovery from those who do not remains underexplored. This retrospective cohort study analyzed 102 children aged 2–18 years with pulmonary TB who were treated at RSUD dr. Zainoel Abidin, Banda Aceh, from January 2024 to January 2025. Patients with comorbidities and incomplete medical records were excluded. Nutritional status was assessed using the CDC 2000 Growth Charts at three time points: baseline, 2 months, and 6 months, and analyzed using Repeated Measures ANOVA (p<0.05). Among the participants, 96 (94.1%) recovered, whereas 6 (5.9%) did not. The mean body weight increased significantly from 21.9 kg at baseline to 25.0 kg at six months (p<0.001), with the proportion of children classified as well-nourished rising from 45.1% to 71.6%. Nutritional trajectories improved significantly over the treatment period (p<0.001), with more consistent gains observed in the recovery group. In conclusion, these findings indicate that six-month anti-tuberculosis therapy (ATT) is effective not only in resolving infection but also in enhancing the nutritional status of children. Monitoring nutritional trajectories may serve as a valuable prognostic indicator for evaluating treatment response and predicting clinical outcomes in pediatric TB.